2013
DOI: 10.5055/jom.2013.0159
|View full text |Cite
|
Sign up to set email alerts
|

Usefulness of the opioid risk tool to predict aberrant drug-related behavior in patients receiving opioids for the treatment of chronic pain

Abstract: Neither the patient-completed nor the physician-completed ORT was strongly predictive of moderate-to-severe ADRB in patients receiving chronic opioid therapy for the treatment of noncancer pain in our pain center.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 0 publications
0
13
0
Order By: Relevance
“…While it would be hoped that individual patient characteristics and risk screening tools might prove useful, when subjected to critical review, only a few individual patient characteristics (often identified in only 1 unreplicated study) helped identify patients at high risk, and no individual patient characteristics, other than the absence of a mood disorder, or screening tools appeared particularly useful for safely identifying patients at lower risk. Instead, most screening tools, including the commonly used Opioid Risk Tool, 35 , 36 were based on lower-quality studies or, when test performance was assessed by calculating LRs, demonstrated poor diagnostic performance.…”
Section: Discussionmentioning
confidence: 99%
“…While it would be hoped that individual patient characteristics and risk screening tools might prove useful, when subjected to critical review, only a few individual patient characteristics (often identified in only 1 unreplicated study) helped identify patients at high risk, and no individual patient characteristics, other than the absence of a mood disorder, or screening tools appeared particularly useful for safely identifying patients at lower risk. Instead, most screening tools, including the commonly used Opioid Risk Tool, 35 , 36 were based on lower-quality studies or, when test performance was assessed by calculating LRs, demonstrated poor diagnostic performance.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, the ORT was used retrospectively to separate patients into low or moderate–high risk categories for aberrant opioid use, but there were no differences in prescribing patterns or number of requested refills. This tool has traditionally been used to stratify patients undergoing management of chronic pain, although its utility has been called into question . There is no well‐established risk stratification tool in the acute pain setting.…”
Section: Discussionmentioning
confidence: 99%
“…Although very effective to treat acute pain, opioids comprise a number of serious adverse events; including misuse, abuse and/or addiction, as well as the possibility of inappropriately prolonged opioid use, and diversion (11,16). Therefore, various screening tools have been developed to assess the potential vulnerability of patients to develop aberrant behaviours.…”
Section: Discussionmentioning
confidence: 99%
“…The ORT is generally recognized by clinicians as a quick way of assessing patient's potential for developing drug-related aberrant behaviours. However, there has been criticism of the validity of the ORT in predicting these risks with accuracy (11). There are other tools that have been developed to predict risks of opioid-related aberrant behaviours (The Screener and Opioid Assessment for Patients with Pain (SOAPP) ® (12,13), and all of these tools agree that patients with a past history of substance use disorder are at higher risk of developing aberrant behaviours after long-term use of opioids; however, several studies have demonstrated that opioid-naïve patients may also display aberrant behaviours and become addicted to prescription opioids (14,15).Therefore, despite many endeavours to make risk assessment in clinical practice, there is relatively little empirical data about the measures' ability to assess and predict risk among opioid-naïve patients.…”
Section: Introductionmentioning
confidence: 99%